The Influence of Academic Supervision and Positive School Culture on Learning Quality in Indonesian Elementary Schools - Finda Pramesti; Nurkolis Nurkolis; Ngurah Ayu Nyoman (Papanda Publisher, 2026)
Learning quality in primary schools refers to the effectiveness of instructional processes in facilitating meaningful, student-centered learning that supports students' cognitive, affective, and psychomotor development. It is shaped not only by teachers' individual competence but also by systemic factors within the school environment. Despite growing recognition of academic supervision and school culture as key drivers of instructional quality, their combined influence at the elementary level remains underexplored. This study employed a quantitative ex post facto design to examine the partial and simultaneous effects of academic supervision (X₁) and positive school culture (X₂) on learning quality (Y) in 60 public elementary schools in Purwodadi District, Grobogan Regency. A sample of 220 teachers was selected through proportional random sampling. Data were collected using validated Likert-scale questionnaires (Cronbach's α ≥ 0.962) and analyzed using multiple linear regression with SPSS version 30. Results indicate that academic supervision (β = 0.485, p < 0.001) and positive school culture (β = 0.479, p < 0.001) each exert positive and significant partial effects on learning quality. Simultaneously, both variables explain 55.1% of the variance in learning quality (R² = 0.551, F = 71.911, p < 0.001), with near-equal effective contributions of 27.7% and 27.4%, respectively. These findings suggest that sustainable improvement in elementary school learning quality requires the simultaneous strengthening of instructional supervision and the cultivation of a positive school culture as co-equal institutional factors supporting effective teaching and learning processes.